العقوبة بالتشهير في الفقه الإسلامي - العبار، سعد خليفة (جامعة بنغازي - كلية التربية بالمرج, 2017)
تتنوع العقوبات في النظام الجنائي بحسب الجرائم والمجرمين وظروفهم والقدر اللازم لردع كل منهم، والأهم من هذا كله فاعلية العقوبة في الحيلولة دون وقوع الآخرين ضحية لهذا المجرم، وهذا ما يتحقق من خلال التشهير به أمام الكافة، والتشهير عقوبة أقرتها الشريعة الإسلامية، إذا روعيت في ذلك الضوابط الشرعية، وفي هذا البحث نعرض بالبيان لمفهوم العقاب بالتشهير والحكم الشرعي للتشهير عموما ثم نبين مدى شرعية العقوبة بالتشهير وطبيعة هذه العقوبة وأحوالها وضوابطها الشرعية.
The penalties in the criminal system vary depending on the crimes, criminals, their circumstances, and the extent necessary to deter them. Most importantly, the effectiveness of the punishment in preventing others from being a victim of this criminal. This is achieved through defamation against all. Defamation is a sanction sanctioned by the Islamic Shari'a, if it takes into account the legal controls. In this paper we present the statement of the concept of punishment by defamation, the legitimate rule of defamation in general, and then show the legitimacy of the penalty defamation, the nature of this penalty, its conditions and legal controls.
Keywords: الجريمة والمجرمون -- العقوبات -- العقوبة بالتشهير -- الشريعة الإسلامية -- الفقه الإسلامى -- أصول الفقه الإسلامى